The unmaking of crime : contexts, pathways, and representations of the processes of desistance on the Parisian ground - Benazeth, Valerian (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book uncovers the evolution of the penology that lies behind such evolutions in France and refers to the most recent theories of desistance from crime to analyse the influence of different criminal justice policies like prison, probation or electronic surveillance over this specific process of change"--
Introduction: beyond 'us' and 'them' -- Understanding knowledge about desistance: The empirical and practical contribution of a continent of research -- Methodology: retracing desistance journeys using in-depth interviews -- Is there a French accent in desistance processes? -- The economics of desistance: experimenting with the limits of its power to deconstruct the cult of money -- Desistance and religion: a passport to redefine one's affiliations? -- The intertwining of addictions in desistance processes: the role of an airlock or a bridge -- Becoming an ordinary citizen again: another anchor for the desistance processes -- The ambivalent effects of prison -- Desistance and probation: the paradox of limited institutional effects -- Desistance and electronic surveillance: leverage with varying degrees of success -- Contextualising and extending knowledge about desistance.
Keywords: Corrections -- France -- History; Criminals -- Rehabilitation -- France -- History; Criminal justice, Administration of -- France -- History; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Penology